The Tall al-Hammam excavations / Volume one. An introduction to Tall al-Hammam with seven seasons (2005-2011) of ceramics and eight seasons (2005-2012) of artifacts - Collins, Steven; Kobs, Carroll M.; Luddeni, Michael C. (Tall al-Hammam Excavations, 2015)
TABLE OF CONTENTS; LIST OF FIGURES; LIST OF TABLES; LIST OF POTTERY PLATES; Bibliography.